Expediting Sustainable Implementation of Safety Measures and Risk Reduction Management - Edwin Jo M. Jardin; Jennifer B. Carillo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study assessed the implementation of safety measures and risk reduction management in Consolatrix College of Toledo City, Inc., Cebu. This study determined the respondents’ age, gender, highest educational attainment, length of years of involvement in CCTC, safety trainings attended.This study assessed the implementation of safety measures, provision of safety facilities and trainings. This study also analyzed the attitude of the respondents towards the school’s implementation of safety management. The findings were taken from 75 respondents composed of 5 administrators, 10 teachers, employees, parents and 40 students. A descriptive research design was used. This study revealed that most of the respondents were adults, female, have at least baccalaureate degree, have been connected to CCTC for more than 5 years and have attended safety trainings. Safety measures were implemented. However, the giving of penalties for breaking safety rules was observed to have less extent. Safety facilities were available and safety trainings were also provided. Still, the provision of adequate budget for safety education was in less extent. The respondents have positive attitude towards the implementation of safety management systems